Bioprocessing strategies for enhanced probiotic extracellular vesicle production: culture condition modulation - Lei, Qingyu; Divakarla, Shiva Kamini; Winsley, Tristrom; Roux, Shaun; Chrzanowski, Wojciech (Frontiers in Bioengineering and Biotechnology, 2024)
Probiotic extracellular vesicles are biochemically active structures responsible for biological effects elicited by probiotic bacteria. Lactobacillus spp., which are abundant in the human body (e.g., gut), are known to have anti-inflammatory and antimicrobial properties, and are commonly used in food products, supplements, and in discovery research. There is increasing evidence that Lactobacillus–derived extracellular vesicles (LREVs) have potent immunomodulatory capacity that is superior to probiotics themselves. However, key mechanistic insights into the process that controls production and thus, the function of LREVs, are lacking. Currently, it is unknown how the probiotic culture microenvironment orchestrates the type, yield and function of LREVs. Here, we investigated how multifactor modulation of the biomanufacturing process controls the yield and biological functionality of the LREVs. To achieve this, we selected Lacticaseibacillus rhamnosus as the candidate probiotic, initially cultivated under traditional culture conditions, i.e., 100% broth concentration and pH 5.5. Subsequently, we systematically modified the culture conditions of the probiotic by adjusting three critical process parameters: (1) culture medium pH (pH 3.5, 5.5 and 7.5), (2) growth time (48 and 72 h), and (3) broth concentration (50% and 10% of original broth concentration). EVs were then isolated separately from each condition. The critical quality attributes (CQA) of LREVs, including physical characteristics (size, distribution, concentration) and biological composition (protein, carbohydrate, lipid), were analysed. Functional impacts of LREVs on human epidermal keratinocytes and Staphylococcus aureus were also assessed as CQA. Our findings show that the production of LREVs is influenced by environmental stresses induced by the culture conditions. Factors like broth concentration, pH levels, and growth time significantly impact stress levels in L. rhamnosus, affecting both the production and composition of LREVs. Additionally, we have observed that LREVs are non-toxicity for keratinocytes, the major cell type of the epidermis, and possess antimicrobial properties against S. aureus, a common human skin pathogen. These properties are prerequisites for the potential application of EVs to treat skin conditions, including infected wounds. However, the functionality of LREVs depends on the culture conditions and stress levels experienced by L. rhamnosus during production. Understanding this relationship between the culture microenvironment, probiotic stress response, and LREV characteristics, can lead to the biomanufacturing of customised probiotic-derived EVs for various medical and industrial applications.